The cost of shareholder activism : LVB shareholders vote out the management - Varkkey, Biju, (SAGE Business cases., 2024)
Lakshmi Vilas Bank (LVB) was established as a private sector bank in 1926 in Tamil Nadu. It was set up to serve the financial needs of the people working in small and medium-sized enterprises (SMEs). LVB got into trouble after shifting focus from funding SMEs to funding big corporates. Initially, it made profits; however, corporates' default hit the bank. LVB also made efforts to merge with various entities, but to no avail. Meanwhile, Institutional Investor Advisory Services published an article capturing LVB's poor corporate governance. The article triggered shareholder activism, thereby creating a leadership vacuum. The case highlights the impact of shareholders activism on LVB's management.